2010
DOI: 10.1080/19424620.2010.533608
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of mother-adolescent relations on the longitudinal association between father and offspring depressive symptoms

Abstract: Little theoretical or empirical attention has been given to factors associated with better or worse outcomes in offspring of depressed fathers. Drawing from interpersonal models of intergenerational depression transmission in children of depressed mothers, the present investigation of adolescents and their families (N = 424) examined maternal warmth and hostility as moderators of the longitudinal association between paternal and adolescent depressive symptoms. Controlling for family demographic variables, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Responses to the hostility subscale were not recoded; higher scores indicated lower hostility. This measure has demonstrated good psychometric properties (e.g., Harold & Conger, 1997; Reeb & Conger, 2010). In the present study, both subscales demonstrated high internal consistency (maternal warmth, α = .92; maternal hostility, α = .89; paternal warmth, α = .93; paternal hostility, α = .90).…”
Section: Methodsmentioning
confidence: 99%
“…Responses to the hostility subscale were not recoded; higher scores indicated lower hostility. This measure has demonstrated good psychometric properties (e.g., Harold & Conger, 1997; Reeb & Conger, 2010). In the present study, both subscales demonstrated high internal consistency (maternal warmth, α = .92; maternal hostility, α = .89; paternal warmth, α = .93; paternal hostility, α = .90).…”
Section: Methodsmentioning
confidence: 99%
“…The neurodevelopmental theory of depression suggests that factors originating during earlier stages of human life are linked with an increased likelihood of depressive symptoms later in life . Among fathers, paternal depression is a risk factor potentially associated with increased risk of depression in their offspring and may be the consequence of the individual or combined influences of genetics and the developmental environment …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among fathers, paternal depression is a risk factor potentially associated with increased risk of depression in their offspring and may be the consequence of the individual or combined influences of genetics and the developmental environment. [3][4][5][6][7][8][9] The association between maternal depression and offspring depression is well investigated, with maternal depression identified as an important risk factor for offspring depression. 10,11 While there is increasing awareness of the role that paternal depression can have in child development and later psychosocial outcomes, this topic has not been as thoroughly researched as the relationship between maternal mental health and that of their offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, the average age of children in studies reviewed for meta‐analyses by Connell and Goodman () and Kane and Garber () was 9.5 and 10.7 years, respectively. Of the limited available data using older samples, several studies have reported increased rates of depression and anxiety among adolescent offspring of depressed fathers (Beardslee, Gladstone, Wright, & Cooper, ; Brennan, Hammen, Katz, & Le Brocque, ; Kane & Garber, ; Klein, Lewinsohn, Rohde, Seeley, & Olino, ; Reeb & Conger, ). In an investigation of parental depression and trajectories of psychopathology in previously depressed adolescents, Rohde, Lewinsohn, Klein, and Seeley () found that depression in fathers was associated with offspring risk of psychosocial impairment—but not depression—in early adulthood.…”
mentioning
confidence: 99%